2023
DOI: 10.12688/f1000research.131212.1
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and satisfaction research pre and during the COVID-19 pandemic: a bibliometric analysis of global scientific literature

Abstract: Background: The study provides a comprehensive analysis of trends of global scientific research, comparing pre-coronavirus disease (COVID 19) and during COVID-19 research in happiness and satisfaction, from 2014 up to 2021. Methods: The study period of the current research was divided into two phases, before the COVID-19 pandemic (1998 documents) and during COVID-19 (2020 until December 18, 2021). The Scopus database was comprehensively searched on relevant publications on Happiness and Satisfaction. Only arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Furthermore, the substantial number of authors involved in multi-authored documents (8893) relative to single-authored documents (89) underscores the prevalence of collaborative research efforts in this domain. Similar results were also presented in the bibliometric analysis conducted by Pang et al [82], where authors for single-authored documents were 375 and 4845 authors for multi-authored documents during COVID-19.…”
Section: Dataset Overviewsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the substantial number of authors involved in multi-authored documents (8893) relative to single-authored documents (89) underscores the prevalence of collaborative research efforts in this domain. Similar results were also presented in the bibliometric analysis conducted by Pang et al [82], where authors for single-authored documents were 375 and 4845 authors for multi-authored documents during COVID-19.…”
Section: Dataset Overviewsupporting
confidence: 85%
“…The analysis reveals a total of 8982 unique authors, who collectively account for 10,257 appearances across the extracted documents. In the bibliometric study conducted by Pang et al [82] on happiness and satisfaction before and during COVID-19, the results showed that there were 5220 unique authors before COVID-19, between 2014 and 2019, and 3520 unique authors during COVID-19 (2020-2022). The data suggest a strong collaborative network among authors in this field.…”
Section: Dataset Overviewmentioning
confidence: 98%
See 1 more Smart Citation